PENGARUH AIR REBUSAN DAUN SIRIH MERAH TERHADAP PENURUNAN GEJALA FLUOR ALBUS PADA WANITA USIA SUBUR - Mila Syari; Novy Ramini Harahap; Pratiwi Nasution; Rauda Rauda; Gita Dwitari (Indonesian Trust Health Journal, 2022)
According to WHO, the number of women in the world in 2015 was 6.7 billion and those who had experienced fluoride albus were around 75%. Meanwhile, data from BPS in North Sumatra in 2014 shows that as many as 75% of women experience vaginal discharge, in Medan City as much as 45% of women experience vaginal discharge. The research objective was to determine the effect of red betel leaf boiled water on the reduction of fluor albus symptoms in fertile aged women at the Dolok Masihul Public Health Center in 2020. The research design was a Quasi Experiment with one group pre test post test without control. The total population was 35 respondents and the sample used purposive sampling as many as 35 respondents. The data used are primary and secondary data. Data analysis used univariate and bivariate using non-parametric using the Wilcoxon test. The results showed that there was an effect of Red Betel Leaf Boiled Water on the Decrease in Symptoms of Fluor Albus in Fertile Women with p value = 0.000 <0.05. The conclusion is that there is the effect of Red Betel Leaf Boiled Water on Decreasing Symptoms of Fluor Albus in Women of Fertile Age at Dolok Masihul Public Health Center in 2020. It is hoped that women couples of childbearing age will increase their knowledge about the benefits of red betel leaves and problems for women of childbearing age to maintain their health. especially for the reproductive section of mothers and for health workers to provide information on the importance of maintaining reproductive organs and applying betel leaf in caring for reproductive organs to the community, especially WUS. Abstrak Menurut WHO jumlah wanita didunia pada tahun 2015 sebanyak 6,7 milyar jiwa dan yang pernah mengalami flour albus sekitar 75%. Data BPS di Sumatera Utara tahun 2014 bahwa sebanyak 75% perempuan mengalami keputihan, di Kota Medan sebanyak 45% perempuan mengalami keputihan. Tujuan Penelitan untuk mengetahui Pengaruh Air Rebusan Daun Sirih Merah Terhadap Penurunan Gejala Fluor Albus Pada Wanita Usia Subur di Puskesmas Dolok Masihul Tahun 2020. Desain penelitian yaitu Quasi Eksperimen dengan one grup pre test post test without control. Jumlah populasi sebanyak 35 responden dan sampel menggunakan Purposive Sampling yaitu sebanyak 35 responden. Data yang digunakan dengan menggunakan data primer dan sekunder. Analisis data menggunakan univariat dan bivariat menggunakan non parametrik dengan uji wilcoxon. Hasil penelitian diperoleh ada pengaruh Air Rebusan Daun Sirih Merah Terhadap Penurunan Gejala Fluor Albus Pada Wanita Usia Subur dengan hasil p value =0.000 <0.05. Kesimpulan ada pengaruh Air Rebusan Daun Sirih Merah Terhadap Penurunan Gejala Fluor Albus Pada Wanita Usia Subur di Puskesmas Dolok Masihul Tahun 2020. Diharapkan kepada wanita pasangan usia subur untuk menambah pengetahuan tentang manfaat daun sirih merah dan permasalahan bagi wanita usia subur untuk menjaga kesehatannya, khususnya bagian reproduksi ibu dan untuk tenaga kesehatan agar memberi informasi pentingnya menjaga alat reproduksi dan mengaplikasikan daun sirih dalam merawat alat reproduksi kepada masyarkat khsususnya WUS.